Aripiprazole augmentation in treating comorbid bipolar disorder and obsessive-compulsive disorder - Amerio, Andrea (Gen Psychiatr, 2018)
Obsessive-compulsive disorder (OCD) is one of the most difficult additional diagnoses to manage in patients with bipolar disorder (BD) since the gold standard treatment for one disease (antidepressants for OCD) can worsen the other. This case report describes the efficacy of aripiprazole augmentation as maintenance therapy in a young patient with comorbid BD-OCD. Our patient presented complete remission of affective and obsessive-compulsive symptoms with remarkable improvement in social and occupational functioning for 24 months. Adverse drug reactions were not severe enough to result in drug discontinuation. In consideration of the important nosological, clinical and therapeutic implications, future research efforts may lead to more grounded guidelines, which are greatly needed in patients with comorbid BD-OCD.